Glucocorticoids inhibit the expression of an inducible, but not the constitutive, nitric oxide synthase in vascular endothelial cells. - Radomski, M W (1990)
Vascular endothelial cells contain a constitutive nitric oxide (NO) synthase that is Ca2(+)-dependent. In addition, we have found that these cells express, after activation with interferon-gamma and lipopolysaccharide, an inducible Ca2(+)-independent NO synthase that is distinct from the constitutive enzyme. The generation of NO by this enzyme was detectable after a lag period of 2 hr, reached a maximum between 6 and 12 hr, and was maintained for the duration of the experiment (48 hr). The expression of the inducible NO synthase was inhibited by the protein synthesis inhibitor cycloheximide, a compound that had no direct effect on the activity of either of the two enzymes. Furthermore, hydrocortisone and dexamethasone, but not progesterone, inhibited the expression of the inducible enzyme, without directly affecting the activity of either enzyme, without directly affecting the activity of either enzyme. The effect of these steroids was inhibited in a concentration-dependent manner by cortexolone, a partial agonist of glucocorticoid receptors. Thus, the inhibition of the induction of an NO synthase by glucocorticoids is a receptor-mediated event involving the inhibition of the synthesis of mRNA for de novo synthesis of this enzyme. The induction of this NO synthase may contribute to the pathophysiology of immunologically based conditions. Furthermore, the inhibition of this induction by anti-inflammatory steroids may explain some of the therapeutic and adverse effects of these compounds.